Studying the effect of Allium sativum and Bunium persicum essential oils on histamine production in Mahyaveh, an Iranian seasoned fish sauce. Issue 1 (28th November 2018) - Hajimohammadi, Bahador; Raeisi, Mojtaba; Eftekhar, Ebrahim; Mohebat, Razieh; Saffari, Azadeh
Abstract: Mahyaveh is a traditional seasoned fish sauce in Iran that its histamine level is above the hazardous limit defined by food safety systems. This study aimed to add Allium sativum ( A. sativum ) and Bunium persicum ( B. persicum ) essential oils (EOs) at four concentrations including 0 (control), 0.1, 1, and 2%, as effective antimicrobial agents to monitor changes in the level of histamine at 30, 60, 90, and 120 days. Histamine ELISA Kit was used for histamine determination and mean values of histamine were compared using SPSS. The level of histamine in 0.1% B. persicum, 0.1% A. sativum, and control at day 30 was 8, 403.05, 10, 596.15, and 16, 339.00 mg/kg, respectively. The results show that the level of histamine in all treatments containing A. sativum and B. persicum EOs at all concentration as well as all days was lower than the control group. Additionally, significantly lower level of histamine was observed in all B. persicum treatment group in compare to A. sativum treatment. While sensory evaluation was considered, no significant differences between the control and treatments in overall acceptance scores were seen. This study suggested that A. sativum and B. persicum EOs at 0.1% concentration could be useful strategy to reduce histamine level in the Mahyaveh. Practical applications: Mahyaveh as a fermented fish sauce in Iran has been proved to contain high levels of histamine which is hazardous for public health. It is necessary to reduce the level of histamine. In the present work, we use two different natural products and monitored its effect on histamine content of Mahyaveh for 120 days. Our results indicated that the addition of low concentration of Allium sativum or Bunium persicum essential oils could effectively reduce histamine level in Mahyaveh without affecting sensory acceptance. This could be considered as practical strategy to reduce potential hazards of histamine in Mahyaveh or other fermented fish sauces.